2021
DOI: 10.3389/fonc.2021.790004
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Evolution of High-Risk Chronic Lymphocytic Leukemia: A Contemporary Perspective

Abstract: Clonal evolution represents the natural process through which cancer cells continuously search for phenotypic advantages that enable them to develop and expand within microenvironmental constraints. In chronic lymphocytic leukemia (CLL), clonal evolution underpins leukemic progression and therapeutic resistance, with differences in clonal evolutionary dynamics accounting for its characteristically diverse clinical course. The past few years have witnessed profound changes in our understanding of CLL clonal evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 170 publications
(260 reference statements)
0
12
0
Order By: Relevance
“…A logistic function was chosen to describe the general behavior of DLBCL cells, as it can be relevant when considering a spatially extended system in which proliferation is constrained by available space [36]. Moreover, logistic growth has been observed in clonal equilibrium associated with chronic lymphocytic leukemia, another hematological malignancy [37]. For initial computational simulations, it was assumed that the resistant cells would have a smaller rate constant than the sensitive variant.…”
Section: The Denominator ([G+r] Mmentioning
confidence: 99%
“…A logistic function was chosen to describe the general behavior of DLBCL cells, as it can be relevant when considering a spatially extended system in which proliferation is constrained by available space [36]. Moreover, logistic growth has been observed in clonal equilibrium associated with chronic lymphocytic leukemia, another hematological malignancy [37]. For initial computational simulations, it was assumed that the resistant cells would have a smaller rate constant than the sensitive variant.…”
Section: The Denominator ([G+r] Mmentioning
confidence: 99%
“…The development of the CRISPR-Cas9 system suggested that researchers might be given a new method for cancer treatment [ 42 ]. Given that cancer is a genetic abnormality caused by a series of genetic alterations, it is reasonable to believe that repairing oncogenic genome/epigenome aberrations using CRISPR-Cas9 could be a promising cancer treatment modality [ 43 ]. Furthermore, by using the CRISPR system, existing anticancer therapies can be improved in terms of high precision and safety, and broad applications including anticancer drug development research are possible [ 44 ].…”
Section: Cancer Therapeuticsmentioning
confidence: 99%
“…The wide range in incidence may be explained by the heterogeneous mutational status of CLL patients from different studies. In fact, specific biomarkers (e.g., NOTCH1, TP53 abnormalities, and trisomy 21) coupled with definite microenvironmental interactions associate to a higher risk of RS transformation ( 5 , 6 ). Disease progression and high-grade transformation are a frequent cause of targeted therapy discontinuation in trial ( 3 , 7 ) and non-trial ( 8 11 ) populations.…”
Section: Introductionmentioning
confidence: 99%